India’s diplomacy in absentia: violence, defense, offense - Datta-Ray, Deep K. (University of California Press, 2023)
The rare occasions when diplomacy does not constitute international politics arise from the presumption there are no other actors or diplomacy’s supplementation. An instance of the former was the Chinese diplomat’s report which led to the first mention of the Roman Empire in Chinese records, thereby expanding awareness and setting the scene for diplomacy with the empire. As for the latter, it is war. Diplomacy therefore expands awareness, and so its field, and continues alongside war and inevitably replaces it. All three, diplomacy, its presumed absence, and supplementation, are International Relations’ (IR) subjects. Diplomacy’s centrality to IR is what makes it vital to Political Science, for IR’s domain of interstate relations is at a minimum related to the intrastate relations studied by the latter. This is now recognized by IR, and so it accounts for interstate relations by referring to the intrastate. What this affirms is the inextricable intermixing of intrastate and interstate politics, and so reiterates the role of diplomacy in animating all politics and why diplomats merit study. Yet when they are studied, imposed categories occlude them and nowhere is this more apparent than in the study of Indian diplomacy. When not riddled with factual errors, conceptual imposition makes for incoherent, emaciated, or morally suspect analysis. For instance, Realist authors use their theory of rationalism, i.e., Realism, to account for Indians and Pakistanis, yet claim both have different rationalities, and all while attenuating actors to materialism and so denying them their culture and history. Meanwhile, Postcolonial authors reduce actors to alien concepts of status at the expense of the material. Underscoring both schools is their infantilizing Indians as learning to do diplomacy from Liberals and then Realists, both understood as past masters, of diplomacy by virtue of being European. Out-of-court at inception then is equality, and so of diplomacy being investigated in terms of its non-Western producers. The price is that their intellectual categories are lost, and so our understanding of international politics enervated. In short, requisite is an intellectual history of diplomacy in producer’s terms rather than that of those who study them.